2008
DOI: 10.1200/jco.2007.14.9260
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Target Inhibition With Dasatinib 100 mg Once Daily Preserves Efficacy and Improves Tolerability in Imatinib-Resistant and -Intolerant Chronic-Phase Chronic Myeloid Leukemia

Abstract: Dasatinib 100 mg once daily retains the efficacy of 70 mg twice daily with less toxicity. Intermittent target inhibition with tyrosine kinase inhibitors may preserve efficacy and reduce adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
453
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 436 publications
(477 citation statements)
references
References 23 publications
16
453
0
8
Order By: Relevance
“…70 To minimize dasatinib-related toxicity while maintaining efficacy, a dose-optimization study was initiated. 74 In that phase 3 trial, 670 patients with imatinib-resistant or imatinib-intolerant CML-CP were randomized to receive 1 of 4 doses of dasatinib: 100 mg once daily, 50 mg twice daily, 140 mg once daily, or 70 mg twice daily. Patients who received dasatinib once daily (100 mg once daily) achieved an MCyR rate comparable to that achieved by patients who received dasatinib twice daily (70 mg twice daily).…”
Section: Dasatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…70 To minimize dasatinib-related toxicity while maintaining efficacy, a dose-optimization study was initiated. 74 In that phase 3 trial, 670 patients with imatinib-resistant or imatinib-intolerant CML-CP were randomized to receive 1 of 4 doses of dasatinib: 100 mg once daily, 50 mg twice daily, 140 mg once daily, or 70 mg twice daily. Patients who received dasatinib once daily (100 mg once daily) achieved an MCyR rate comparable to that achieved by patients who received dasatinib twice daily (70 mg twice daily).…”
Section: Dasatinibmentioning
confidence: 99%
“…It is noteworthy that the rates of grade 3/4 hematologic and nonhematologic toxicities, including pleural effusions, were decreased with 100 mg once-daily dasatinib dosing. 74 Currently, a once-daily dose of 100 mg is approved for patients with CML-CP based on these findings. Dasatinib at 70 mg twice daily and 140 mg once daily currently are dosing options for patients with CML-AP and CML-BC.…”
Section: Dasatinibmentioning
confidence: 99%
“…Second-line therapy with dasatinib is further supported by an open-label phase III trial of patients with imatinib-resistant or -intolerant chronic phase CML, with long-term follow-up to 6 years [55,56]. The trial showed that dasatinib 100 mg once daily (OD) had comparable efficacy to the licensed 70 mg twice daily (BID) dose, but with a more favorable tolerability profile, including significantly lower rates of grade 3/4 thrombocytopenia and all-grade pleural effusion [53].…”
Section: Dasatinibmentioning
confidence: 99%
“…ALL) at a dosage of 70 mg twice daily. Results from a recent phase III dose-optimization study recently prompted a change in the recommended daily dose for patients with CP CML [70].…”
Section: F359mentioning
confidence: 99%